2011
DOI: 10.1177/039463201102400209
|View full text |Cite
|
Sign up to set email alerts
|

Complement System and Rheumatoid Arthritis: Relationships with Autoantibodies, Serological, Clinical Features, and Anti-TNF Treatment

Abstract: The first two authors contributed equally to this work Autoantibodies (rheumatoid factor, RF; anti-citrullinated-protein antibodies,ACPA) and complement system are involved in rheumatoid arthritis (RA). ACPA and anti-TNF agents are capable of in vitro modulating complement activity. We investigated the relationships between complement, autoantibodies, and anti-TNF treatment in vivo. One-hundred fourteen RA patients (89F/25M), diagnosed according to 1987 ACR criteria, and 30 healthy controls were enrolled. Sero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 27 publications
4
26
0
Order By: Relevance
“…Our results were in agreeing with study by Di Muzio et al 27 , and disagree with study by Gupta et al which reported that the levels of anti-MBL antibodies were still positive and high in negative cases of RF and CRP 26 . As regard ACPA, there was no association between positive ACPA and the levels of anti-MBL autoantibodies, in which the meanSD of anti-MBL levels for ACPA positive cases was 376.8257 ng/ml, and for negative ACPA were 415.4208 ng/ml.…”
Section: Issn: 2456-8058supporting
confidence: 52%
“…Our results were in agreeing with study by Di Muzio et al 27 , and disagree with study by Gupta et al which reported that the levels of anti-MBL antibodies were still positive and high in negative cases of RF and CRP 26 . As regard ACPA, there was no association between positive ACPA and the levels of anti-MBL autoantibodies, in which the meanSD of anti-MBL levels for ACPA positive cases was 376.8257 ng/ml, and for negative ACPA were 415.4208 ng/ml.…”
Section: Issn: 2456-8058supporting
confidence: 52%
“…Moreover, 62.5% of the aut-I-AAE patients had autoimmune thyroid disorders, representing a prevalence of 5.6% in the whole cohort. Clinical associations between urticarial/recurrent AE and autoimmune thyroid disease [24,46] , connective-tissue disorders, and systemic vasculitis are reported in the literature [47,48] . Defining a cause-effect relation between autoimmune disease and AE is still difficult.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 The contribution of CRP and IL-6 to general inflammation in IBD is equally well-recognized. 25 In addition to circulating IFN-a levels being elevated in IBD, there is a significant increase in IFN-a levels in active IBD when contrasted with inactive disease.…”
Section: Discussionmentioning
confidence: 99%